Improvement Branch Line Coupler Isolation in S Band Frequency - Barnadi, Yudi; Agustian, Yanyan; Hasan, Fuad (International Journal of Engineering and Technology, 2018)
In this paper, the research was conducted to investigate the effects of optimization dimension to the isolation value of the Branch line coupler. The isolation is very important because it affects to the performance of the duplexer. The smaller value the better isolation performance of the duplexer. This research is carried out by modifying the length and width of the channels of the impedance of the Coupler. In this experiment, Branch-Line coupler is designed in the form of microstrip and fabricated using the FR-4 substrate that has a dielectric constant of 4.6, thickness of 1.3 mm, and 3 GHz operating frequency. To get the optimization value of the isolation characteristic, impedance channel must be modified, which are the length and width of the arms series (Z0 = 50 Î©), the length and width of the arms series (Z0 = 35.35 Î©), and the length and width of the arms shunt (Z0 = 50 Î©). The optimized result of the isolation is -67,786 B